Relationship Of Nutritional Status With Degree And Type Of Anemia In Vegetarian - Santoso, Yuliana S; Dewi, Dewa AL; Jong, FX Himawan H. (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: A vegetarian that consumes only plant foods is at risk for anemia due to nutritional deficiencies, especially iron and vitamin B12. Aim : to identify the level of nutritional intake, nutritional status, degree of anemia and type of anemia in a vegetarian group and to analyze the relationship between nutritional status with degree and type of anemia. Method : This study used analytic research, with correlational study, through cross sectional approach. The sampling technique of this research was purposive sampling at Vihara Thien Bao (Maha Vihara) with sample of 38 people including inclusion and exclusion criteria. Data were analyzed by using Rank Spearman test to measure the correlational relationship between nutritional status with degree of anemia and the contingency coefficient test measure the correlational relationship between nutritional status with type of anemia. Result : Intake of energy (71.89%), carbohydrate (74.56%), fat (68.04%), protein (134.38%), vitamin B12 (98.83%) and iron (25,04%) for men. Intake of energy (65,42%), carbohydrate (69,21%), fat (63,94%), protein (100,48%), vitamin B12 (45,30%) and iron (27,67%) for women. These data were compared with RDA. P value for nutritional status correlation analysis with degree of anemia was 0,639 and p value for nutritional status correlation analysis with type of anemia was 0,851. Conclusion : There was a deficit of energy, carbohydrate, fat, and iron in both gender. Protein intake was excessive in man and normal in woman. Iron and vitamin B12 intake were adequate in man and deficient in woman. Energy intake was deficient in man and very deficient in women. The nutritional intake was less likely cause anemia. There was no correlation between nutritional status with degree and type of anemia